2015
DOI: 10.1111/tpj.12825
|View full text |Cite
|
Sign up to set email alerts
|

Light stress and photoprotection in Chlamydomonas reinhardtii

Abstract: SUMMARYPlants and algae require light for photosynthesis, but absorption of too much light can lead to photo-oxidative damage to the photosynthetic apparatus and sustained decreases in the efficiency and rate of photosynthesis (photoinhibition). Light stress can adversely affect growth and viability, necessitating that photosynthetic organisms acclimate to different environmental conditions in order to alleviate the detrimental effects of excess light. The model unicellular green alga, Chlamydomonas reinhardti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
282
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 312 publications
(291 citation statements)
references
References 207 publications
(334 reference statements)
6
282
0
3
Order By: Relevance
“…In addition, it has been reported that, in mixotrophic conditions, PSII is more photoprotected than in photoautotrophic conditions showing less 1 O 2 production . The decrease of 1 O 2 under mixotrophic growth might be responsible to some extent for the overall higher Chl/ cell content in mixotrophic compared with photoautotrophic conditions, as an accumulation of 1 O 2 is one of the main triggers for the down-regulation of the photosynthetic genes (Erickson et al, 2015).…”
Section: The Composition Of the Photosynthetic Apparatus Depends On Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been reported that, in mixotrophic conditions, PSII is more photoprotected than in photoautotrophic conditions showing less 1 O 2 production . The decrease of 1 O 2 under mixotrophic growth might be responsible to some extent for the overall higher Chl/ cell content in mixotrophic compared with photoautotrophic conditions, as an accumulation of 1 O 2 is one of the main triggers for the down-regulation of the photosynthetic genes (Erickson et al, 2015).…”
Section: The Composition Of the Photosynthetic Apparatus Depends On Tmentioning
confidence: 99%
“…In order to survive and grow, these organisms have developed various photoacclimation mechanisms operating on different time scales that protect the cell from photodamage. In the green alga Chlamydomonas reinhardtii, these mechanisms vary from negative phototaxis and multicomponent nonphotochemical quenching (NPQ) to a number of physiological and biochemical changes (Erickson et al, 2015). C. reinhardtii cells are around 10 mm in diameter, and a large part of their total volume is occupied by a single horseshoe-shaped chloroplast (Sager and Palade, 1957).…”
mentioning
confidence: 99%
“…To avoid photodamage, photosynthetic light harvesting is regulated by nonphotochemical quenching (NPQ), which allows dissipation of harmful excess energy as heat through its qE (energy-dependent nonphotochemical quenching) component (1)(2)(3)(4)(5)(6). Specialized members of the light harvesting complex (LHC) protein family, such as Photosystem II Subunit S (PSBS) in higher plants or members of the LHC Stress-Related (LHCSR) family in mosses and algae, are central to qE (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…It is known to consist of several components each with a different induction and relaxation time (Müller et al 2001, Erickson et al 2015. One of these components (qI) is described as a sustained thermal dissipation mechanism that is slowly reversible (range of hours)…”
Section: Possible Explanations For the Discrepancy Between The Model mentioning
confidence: 99%
“…probably due to a combination of photoprotection and photodamage (Müller et al 2001, Lambrev et al 2010, Erickson et al 2015. Reaching maximum dissipation capacity involves the biosynthesis of enzymes and pigments such as zeaxanthin.…”
Section: Possible Explanations For the Discrepancy Between The Model mentioning
confidence: 99%